Development and evaluation of a robotic system for lumbar puncture and epidural steroid injection - Lu, Jiaxin; Huang, Zekai; Zhuang, Baiyang; Cheng, Zhuoqi; Guo, Jing; Lou, Haifang (Frontiers in Neurorobotics, 2023)
Lumbar puncture is an important medical procedure for various diagnostics and therapies, but can be hazardous due to individual variances in subcutaneous soft tissue, especially in the elderly and obese. Our research describes a novel robot-assisted puncture system that automatically controls and maintains the probe at the target tissue layer through a process of tissue recognition. The system comprises a robotic system and a master computer. The robotic system is constructed based on a probe consisting of a pair of concentric electrodes. From